Auf dem Weg zu mehr Präzision in der Hirntumortherapie: Möglichkeiten und Grenzen der MR-Bildgebung = BildgebungTowards more precision in the therapy of brain tumors : possibilities and limits of MRI - Radbruch, Alexander; Hattingen, Elke (Der Nervenarzt, 2015)
SummaryDue to the introduction of advanced functional and spectroscopic magnetic resonance (MR) sequences, MR imaging has gained significant importance in neuro-oncology. In contrast to recent years when neuro-oncological imaging was mostly limited to contrast-enhanced T1-weighted images, advanced MR methods provide direct visualization and assessment of tumor pathophysiology. This article summarizes the most relevant MR methods for neuro-oncological imaging and highlights the pathophysiological background as well as potential clinical applications. Ultimately, this article gives a glimpse into the future and introduces potential applications of ultra-high field MRI.
Gesehen am 27.04.2017